2004
DOI: 10.1145/974750.974754
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating XPath evaluation in any RDBMS

Abstract: This article is a proposal for a database index structure, the XPath accelerator, that has been specifically designed to support the evaluation of XPath path expressions. As such, the index is capable to support all XPath axes (including ancestor, following, preceding-sibling, descendant-or-self, etc.). This feature lets the index stand out among related work on XML indexing structures which had a focus on the child and descendant axes only. The index has been designed with a close eye on the XPath semantics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
106
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(106 citation statements)
references
References 16 publications
(18 reference statements)
0
106
0
Order By: Relevance
“…PF/Tijah creates a full-text index on top of Pathfinder's pre/post encoding of XML files [5]. Instead of assigning a pre-order value to complete textnodes as done by the Pathfinder, the Tijah full-text index enumerates each single term.…”
Section: Efficiencymentioning
confidence: 99%
“…PF/Tijah creates a full-text index on top of Pathfinder's pre/post encoding of XML files [5]. Instead of assigning a pre-order value to complete textnodes as done by the Pathfinder, the Tijah full-text index enumerates each single term.…”
Section: Efficiencymentioning
confidence: 99%
“…In general, to process multi-step (k > 1) XPath path expressions, the system generates an SQL query that is nested to depth k, and then this scheme is improved to generate an SQL query involving a k-way self-join [19]. XTRON reduces the number of self-joins using the reverse arithmetic encoding.…”
Section: Translation Of Path Expressionsmentioning
confidence: 99%
“…This is surprising as these path expressions make query authoring (they allow avoiding recursive views) easier and can be implemented efficiently as research on these constructs for XML query languages has shown. In particular, unrestricted closure path expressions can be implemented nearly as efficiently as basic path expressions using, e.g., tree labeling schemes [48] or closure indices.…”
Section: Triple Patterns Vs Path Expressionsmentioning
confidence: 99%